Development of intangible cultural heritage as a sustainable tourism resource: the intangible cultural heritage practitioners' perspectives. Issue 5 (2nd November 2019) - Kim, Soojung; Whitford, Michelle; Arcodia, Charles
ABSTRACT: Authentic intangible cultural heritage (ICH) provides a community with a unique selling point in the globally competitive tourism industry. The process of commodification of ICH, however, has threatened its authenticity and thus sustainable tourism approaches are required to achieve successful transmission and promotion of ICH as a sustainable tourism resource. This paper explores the priorities of ICH practitioners in relation to the development of ICH as a sustainable tourism resource, by utilising South Korea as a case study. The results revealed that from the ICH practitioners' perspectives, authenticity is a holistic notion integrating the transmitted customs, inherited meanings and the practitioners' identities. ICH practitioners agree with the potential positive symbiotic relationship between transmission of authentic ICH and promotion of ICH as a tourism resource. To achieve the positive symbiotic relationship, locals' awareness of ICH, ICH practitioner empowerment and parallel development between tourism development and transmission of ICH are necessary. To date, the practitioner approach to the authenticity of ICH and ICH as a sustainable tourism resource is little explored in the literature, thus this paper makes a valuable addition to the area of sustainable heritage tourism.